Nanofluid stability and physical properties of alumium oxide nanoparticles in aqueous solutons of [HMIM]LS - Doliente, Stephen Salve (2012)
Nanofluids or nanoparticle fluid suspensions are the next generation heat transfer fluids that can further the development of ultrahigh performance and energy-efficient liquid cooling systems. However, they have limited colloidal stability which can affect their performance and properties. This study tested a greener ionic liquid, 1-hexyl-3-methylimidazolium lauryl sulfate (HMIM)LS, as a dispersant for aluminum oxide (Al2O3) nanoparticles in water to improve its stability and determine its effect on the physical properties. Absorbance and zeta potential as measures of stability were tracked in a one-week period. Then the influence if the ionic liquid on density, surface tension and viscosity was measured. Results showed that [HMIM]LS was an effective dispersant. the average % difference in the absorbance of the nanofluid with [HMIM]LS to the control remained was consistently higher from 10.2.32% day 0 to 3674.04% on day 7. An increasing averaged absolute value of zeta potential was measured from -19.23 mV on day 0 to -36.9 mV on day 7, also indicated it as a stable dispersion. The density, surface tension and viscosity of 0.25, 0.50 and 0.75 %v/v AL2O3 nanoparticles in ultrapure water and 30mM [HMIM]LS were measured at 25, 50 and 75 deg.C. The densities of nanofluids with and without [HMIM]LS were not significantly different. On the other hand, the surface tensions and viscosities of nanofluids with [HMIM}LS were at an average of 56.21% lower and 11.81% higher than that of control, respectively.
Thesis (M.S. in Energy Engineering)--University of the Philippines, Diliman
Keywords: Nanofluids; Aluminum oxide; Aqueous solutions